Development of generation special short articles for the given topic - S D, Kulik; A N, Belov; K I, Matveeva (International Journal of Engineering and Technology, 2018)
The subject area and reviewed various sources of information relevant to a given topic will be considered. For implementation of algorithm of generation of the texts was chosen the C# language, as it has a large number of advantages compared to other programming languages, and it also has many libraries which it would be convenient to use in solving a given task. The text presents the structure of the generated article and the scheme of the developed algorithm for the application. Also it describes the structures that are used to implement such applications. The implementation of algorithm of generation of short articles on a given topic in English was discussed. Familiarization with the application was conducted and the results of generation were shown.  It was shown that the generated articles have a good percentage of the plagiarism by experimental studies. It was shown that the articles would not be repeated even more than 50 generations, as a result of tests. Also was shown the implementation of the program on C# language, it’s interface, design generation and design of the English translation.